2019
DOI: 10.1111/jnc.14887
|View full text |Cite
|
Sign up to set email alerts
|

Glial pathology in a novel spontaneous mutant mouse of the Eif2b5 gene: a vanishing white matter disease model

Abstract: Vanishing white matter disease (VWM) is an autosomal recessive neurological disorder caused by mutation(s) in any subunit of eukaryotic translation initiation factor 2B (eIF2B), an activator of translation initiation factor eIF2. VWM occurs with mutation of the genes encoding eIF2B subunits (EIF2B1, EIF2B2, EIF2B3, EIF2B4, and EIF2B5). However, little is known regarding the underlying pathogenetic mechanisms or how to treat patients with VWM. Here we describe the identification and detailed analysis of a new s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…10 eIF2α phosphorylation is reduced, probably as a consequence of an increased GADD34-mediated negative feedback loop. [10][11][12][13] This reduction may be a compensatory measure for intrinsically reduced activity of mutated eIF2B. Our findings point to a constitutively and increasingly deregulated ISR in VWM that contribute to the chronic neurological deterioration.…”
Section: Introductionmentioning
confidence: 62%
“…10 eIF2α phosphorylation is reduced, probably as a consequence of an increased GADD34-mediated negative feedback loop. [10][11][12][13] This reduction may be a compensatory measure for intrinsically reduced activity of mutated eIF2B. Our findings point to a constitutively and increasingly deregulated ISR in VWM that contribute to the chronic neurological deterioration.…”
Section: Introductionmentioning
confidence: 62%
“…Moreover, it has been shown that in older VWMD affected patients, Bergmann glial somata are translocated to the molecular layer whereas they should be located close to Purkinje cells, this translocation representing a hallmark of VWMD for Dooves et al [13,16]. This disease marker has also been reported in a spontaneous mutant mouse in the Eif2b5 gene called the "toy mouse" [17]. In the two foetuses, virtually absent Bergmann glia somata and processes suggested a defect of Bergmann glia development and/or maintenance from early stages of gestation.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, modulation of the brain level of this protein by chronic Li has been reported in rats 29 . Furthermore, a mutant mouse of the Eif2b5 gene may represent a model for vanishing white matter disease 30 , hence showing a crucial role of this gene in some brain disorders. A long intergenic noncoding RNA is also included in this DNA methylation signature.…”
Section: Discussionmentioning
confidence: 99%